Integration of the Functional Testing with the General Theory of the Technical Diagnosis - Mihai POPESCU (Informatică economică, 2010)
The paper goal is to integrate the software reliability into the general theory of the reliability, this thing being a natural approach, perfectly justified by the core concepts governing the two areas.